The Urgency of Comprehensive and Integrated Digital Asset Regulation - Francisca Romana Nanik Alfiani (Syntax Corporation Indonesia, 2024)
Cryptocurrency has grown rapidly since it was first introduced to the public. Many countries, including Indonesia, have begun to adopt special regulations for cryptocurrencies in response to the exponential growth and penetration of cryptocurrencies in the traditional financial system. Regulations aim to protect investors, ensure economic stability, and prevent illegal activities such as terrorism, money laundering and tax evasion. In January 2023, Law Number 4 of 2023 concerning Development and Strengthening of the Financial Sector (